Higher serum concentrations of vimentin and DAKP1 are associated with aggressive breast tumour phenotypes in Ghanaian women - Benjamin Arko-Boham; Justice Tanihu Lomotey; Emmanuel Nomo Tetteh; Emmanuel Ayitey Tagoe; Nii Ayite Aryee; Ewurama Ampadu Owusu; Isaac Okai; Richard Michael Blay; Joe-Nat (BMC, 2017)
Abstract Background Breast cancer, the most commonly diagnosed cancer among women and leading cause of cancer-related deaths worldwide, exhibits aggressive behavior in indigenous African women evidenced by high histologic grade tumours with low hormone receptor positivity. Aggressive breast cancers grow quickly, easily metastasize and recur and often have unfavourable outcomes. The current study investigated candidate genes that may regulate tumour aggression in Ghanaian women. We hypothesize that increased expression and function of certain genes other than the widely-held view attributing breast cancer aggression in African populations to their younger population age may be responsible for the aggressive nature of tumours. Methods Employing ELISA, we assayed for vimentin and death-associated protein kinase 1 (DAPK1) from thawed archived (stored at -80 °C) serum samples obtained from 40 clinically confirmed Ghanaian breast cancer patients and 40 apparently healthy controls. Patients' clinical records and tumour parameters matching the samples were retrieved from the database of the hospital. ANOVA was used to compare means of serum protein concentration among groups while Chi-square analysis was used for the categorical data sets with p-value ≤0.05 considered significant. Multiple logistic regression analysis was conducted to determine the association between protein concentration and tumour parameters. Results Of the 80 samples, 27 (33.8%) and 53 (66.2%) were from young (<35 years) and old (≥35 years), respectively. Vimentin and DAPK1 concentration were higher in patients than controls with higher levels in "young" age group than "old" age group. Vimentin concentration was highest in grade 3 tumours followed by grade 2 and 1 but that for DAPK1 was not significant. For vimentin, tumour area strongly correlated with tumour grade (r = 0.696, p < 0.05) but weakly correlated with tumour stage (r = 0.420, p < 0.05). Patient's age correlated with DAPK1 concentration (r = 0.393, p < 0.05). DAPK1 serum levels weakly correlated with cancer duration (r = 0.098, p = 0.27) and tumour size (r = 0.40, p < 0.05). Conclusion Serum concentration of Vimentin and DAPK1 are elevated in Ghanaian breast cancer patients. This may be partly responsible for aggressive nature of the disease among the population. Vimentin and DAPK1 should be explored further as potential breast cancer biomarkers in Africans.